2014
DOI: 10.4161/epi.27585
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic deregulation in pediatric acute lymphoblastic leukemia

Abstract: Similar to most cancers, genome-wide DNA methylation profiles are commonly altered in pediatric acute lymphoblastic leukemia (ALL); however, recent observations highlight that a large portion of malignancy-associated DNA methylation alterations are not accompanied by related gene expression changes. By analyzing and integrating the methylome and transcriptome profiles of pediatric B-cell ALL cases and primary tissue controls, we report 325 genes hypermethylated and downregulated and 45 genes hypomethylated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 59 publications
5
41
0
Order By: Relevance
“…Genome-wide DNA methylation profiles are commonly altered in pediatric ALL (41). It has been demonstrated that hypermethylation of multiple genes may be involved in the relapse of childhood ALL (42).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide DNA methylation profiles are commonly altered in pediatric ALL (41). It has been demonstrated that hypermethylation of multiple genes may be involved in the relapse of childhood ALL (42).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, other epigenetic regulators, such as DNA methylation, histone modifications and long noncoding RNAs could also have a role in the development of L-ASP hypersensitivity. In this line, it has been already demonstrated that ALL ETV6-RUNX1 subtype displays hypermethylation of ASNS [91], which was associated with a higher sensitivity of leukemic cells to L-ASP [92] in ETV6-RUNX1 patients [93]. This developing field of pharmacoepigenetics has started to produce promising results and epigenetic variants have great potential to be used as biomarkers for personalized therapy.…”
Section: Conclusion and Future Perspectivementioning
confidence: 76%
“…Such alterations represent underused biomarkers in oncology capable of discriminating cancers of different tissue types, subtyping cancers, and adding independent prognostic information to cancer diagnosis (18,19 ). Here we present 2 complementary techniques that enable (a) regional multiplexing of DNA methylation (multiplexed EpiTYPER) facilitating robust diagnosis/prognosis and subtyping and (b) detection of rare DNA methylation events (methylSABER) that will facilitate disease tracking.…”
Section: Discussionmentioning
confidence: 99%